Kesulitan siswa dalam menyelesaikan aljabar linear - sari, Rasida Aulia; Tarigan, Citra Kesuma (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2024)
This research aims to identify and analyze the difficulties experienced by students in solving linear algebra problems. This study was conducted involving high school students as research subjects, who were given a series of questions to solve and documented theprocess of solving them. The method used is qualitative analysis of student answers and structured interviews with several students to gain deeper insight into the difficulties they experience. This research focuses on understanding the basic concepts of linear algebra, the ability to formulate and solve linear equations in one variable, as well as the skills to apply algebraic concepts in the context of real situations. The results of the analysis show that students face various difficulties, including difficulty in understanding mathematical notation, difficulty in converting language sentences into algebraic form, and difficulty in applying basic mathematical formulas and operations correctly. Factors that influence this difficulty include lack of adequate practice, confusion in the steps for solving problems, and lack of confidence in dealing with algebra material.